Optical and thermoluminescence properties of samarium or dysprosium doped lithium borate glass [electronic resource] - Raghda Saifeddin Said Dawaud, 1986-, author (2015)
Thesis (Sarjana Kejuruteraan (Physic)) - Universiti Teknologi Malaysia, 2015